The Efficacy of Ginsenoside Rg3 Combined with First-line Chemotherapy in the Treatment of Advanced Non-Small Cell Lung Cancer in China: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Peng, Ze; Wu, Wen Wen; Yi, Ping (Frontiers in Pharmacology, 2021)
Background: For advanced non-small cell lung cancer (NSCLC) patients, first-line chemotherapy is the main treatment in the clinic despite its efficacy is limited and adverse effects are always inescapable. Ginsenoside Rg3, an anti-cancer active ingredient by suppressing angiogenesis, has been increasingly widely used as an adjuvant in first-line chemotherapy for advanced NSCLC to optimize treatment in China. However, no comprehensive meta-analyses have been conducted to estimate the efficacy and safety of the therapy combining ginsenoside Rg3 and first-line chemotherapy in advanced NSCLC patients. Methods: Randomized controlled trails using a combination of first-line chemotherapy and ginsenoside Rg3 for advanced NSCLC patients were searched and selected from six databases. The Cochrane Risk of Bias tool was used to assessed the quality of these selected original researches. And we used Review Manager 5.3 and STATA to analyze the data. Results: Twenty-two RCTs that matched our selection criteria with a number of 2202 patients were included in our review. The results showed that compared with first-line chemotherapy alone, the combination of ginsenoside Rg3 and first-line chemotherapy could better improve the objective response rate (ORR) (RR [95% CI], 1.44 [1.27, 1.63], p < 0.00001 ), the disease control rate (DCR) (RR [95% CI], 1.24 [1.12, 1.38], p < 0.0001), karnofsky performance status (KPS) (RR [95% CI], 1.62 [1.42, 1.84], p < 0.00001), one-year survival rate (RR [95% CI], 1.49 [1.08, 2.06], p = 0.01), two-year survival rate (RR [95% CI], 6.22 [1.68, 22.95], p = 0.006), weight change (RR [95% CI], 1.31 [1.04, 1.66], p = 0.02), and higher reduce the VEGF levels (RR [95% CI], -2.21 [-4.03, -0.38], p = 0.02), the incidence of gastrointestinal reactions (RR [95% CI], 0.66 [0.47, 0.93], p = 0.02) and bone marrow suppression (RR [95% CI], 0.43 [0.30, 0.61], p < 0.00001). Conclusion: Ginsenoside Rg3 can enhance drug efficacy and reduce drug-induced toxicity from chemotherapy. These findings provide helpful information for clinicians indicating that a therapy combined of ginsenoside Rg3 and first-line chemotherapy may be used to optimal the treatment of advanced NSCLC.